Production and Application of Aggregate Manganese Zeolite Greensand using Post Cartridge Micron as Absorbent Fe and Mn Ions. Issue 1 (May 2019) - Ricky Wijaya, Anugrah; Wonorahardjo, Surjani; Kartika Kusumaningrum, Irma; Alfini'matin, Dwi; Hertanto, Pungky; Avila, Shila; Daupor, Hasan; Hossain, Md. Sazzad; Hendrik Sanjaya, Eli
Abstract: The purpose of this study was to produce an aggregate of fine manganese greensand and its applications using micron cartridge design for absorbing Fe 3+ and Mn 2+ ions in the well water affected by the Lapindo mud. The fine manganese greensand was made using the flame spray pyrolysis. The combination of aggregate material and the bulk manganese greensand were performed with the adding filler with the varied compositions of CaO, CaCO3, and white cement as the adhesive. Characterization of topography, morphology, and composition of aggregate manganese greensand was performed using SEM-EDX (Scanning Electron Microscope-Energy Dispersive X-Ray). Applications of the aggregate manganese greensand and activated carbon were designed in several post cartridge microns for well water samples. Initial and final measurement the concentration of Fe and Mn solution using a calibration curve by AAS method (Atomic Absorbance Spectrophotometer). The results showed that the aggregate A with a composition of fine manganese greensand: bulk manganese greensand: CaCO3 : CaO and white cement is 2:5:1:1:1:1 and aggregate B (3:4:1:1:1) absorbed maxima ions of Mn (97.5%) and Fe (80.3%) in the well water sample, respectively. Besides, the profile of spectrum SEM-EDAX indicated the aggregate A and B interacting with filler which showed the active situs as exchange cation for absorbing Fe 3+ and Mn 2+ ions.